Analysis of physio-biochemical indices for growth and yield of groundnut (Arachis hypogaea L.): Analysis of physio-biochemical indices for growth and yield of groundnut (Arachis hypogaea L.) - S R MORE; P H DESHMUKH; G R LOTHE (Journal of Oilseeds Research, 2023)
The present study on the topic was performed at AICRP on groundnut, M.P.K.V., Rahuri, (M.S.) during summer 2021.The experiment was laid out in Randomized Block Design with three replication including sixteen genotypes. The groundnut genotypes with highest rate of photosynthesis and transpiration processes are higher in yielding. Correlation studies revealed that number of mature pods/plant and 100 kernels weight (g), showed maximum influence on dry pod yield (g/plant). The genotypes Phule Unnati, ICGV-15311 and ICGV-15303 showed higher yielding ability and HI (%).